Visual Characterization of Airless Water Spray Jet Breakup and Vortex Clouds Formation at Elevated Temperature and Pressure - Naz, M.Y. (Springer Verlag, 2014)
Most of the Newtonian fluids when heated close to their boiling points exhibit very complex spray structures where vortex clouds may occur due to turbulence in the flow. The objective of the study was to observe the spray jet dynamics and the vortex cloud formation during the atomization of the water at elevated temperature and pressure. For this purpose, visual and comparative studies were conducted on full cone water spray pattern generated by three axi-symmetric spray nozzles of different exit diameters. Using a high-speed camera, the jet breakup dynamics were visualized as a function of water heating temperature and load pressure. The image analysis confirmed the strong influence of the nozzle orifice diameters and processing parameters on spray structure and characteristics. The spray cone angle and width did not vary significantly with increasing Reynolds and Weber numbers at early injection phases leading to increased macroscopic spray propagation. The discharge coefficient, mean flow rate and mean flow velocity were significantly influenced by the load pressure, but less affected by temperature. The fine-scale image analysis also predicted the formation and decay of the semi-torus-like vortex clouds in the spray structures near the water boiling point. For smallest used orifice diameter, these vortex clouds were seen clearly above 1Â bar water pumping pressure and at 90Â°C heating temperature. Â© 2014, King Fahd University of Petroleum and Minerals.